2009
DOI: 10.1111/j.1600-0714.2009.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of proinflammatory and immunoregulatory cytokines by inflammatory cells from periapical lesions in culture

Abstract: Symptomatic lesions are characterized by higher production of proinflammatory cytokines. Immunoregulatory cytokines are more important for suppression of inflammation in asymptomatic lesions and in this context the effect of TGF-beta is more potent and different from IL-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
5
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 41 publications
5
74
5
10
Order By: Relevance
“…The morphological analysis showed that periapical granulomas exhibited higher grades of inflammatory infiltrate than the cysts, but this significant difference was not associated with the scores attributed to the immunohistochemical expression of TGF-β1 and MMP-9. In contrast, Gazivoda et al 10 used a fluorescent bead immunoassay and/or ELISA to prove that immunoregulatory cytokines such as TGF-β are more important for suppression of inflammation in asymptomatic lesions. Based on this finding, the effect of TGF-β was stronger than that of IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The morphological analysis showed that periapical granulomas exhibited higher grades of inflammatory infiltrate than the cysts, but this significant difference was not associated with the scores attributed to the immunohistochemical expression of TGF-β1 and MMP-9. In contrast, Gazivoda et al 10 used a fluorescent bead immunoassay and/or ELISA to prove that immunoregulatory cytokines such as TGF-β are more important for suppression of inflammation in asymptomatic lesions. Based on this finding, the effect of TGF-β was stronger than that of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence suggests that these lesions are the result of a long-term endodontic infection or pulp necrosis leading to a progressive immune/inflammatory response, whose persistence in periapical tissues can result in the resorption of the surrounding bone and reactivation of epithelial cell rests of Malassez 10,21,22 ; which are probably the main source of the epithelial lining of radicular cysts. 9 In fact, it seems that this persistent, chronic inflammation and destruction of bone depends on the inability of a host defense to eradicate the infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic PLs stand for granulomatous inflammation, where the process of exacerbation (symptomatic PLs) and their restriction (asymptomatic PLs) are present (2). It has been shown that the symptomatic PLs are characterized by the upregulation of adhesive molecules, chemotactic factors (3), T helper (Th)1 and Th17 cytokines as well as bone resorptive cytokines such as interleukin (IL)-1, IL-6, and tumour necrosis factor (TNF)-α (2,4). On the other hand, the generation of asymptomatic PLs is followed by the Th2 immune response, which promotes PL chronicity with restriction of inflammation (5).…”
Section: Introductionmentioning
confidence: 99%